Solving the Grid-to-Ground Problem when Using High Precision GNSS in Archaeological Mapping. Issue 2 (May 2014) - Limp, William (Fred); Barnes, Adam
Abstract: Increasingly, high-precision GPS/GNSS (global positioning system/global satellite navigation system) based real-time-kinematic methods are being used in the mapping of archaeological sites. However, when utilizing high-precision satellite-based methods for archaeological location purposes, there is a significant but usually unanticipated problem that must first be addressed if accurate measurements are to be made. Simply put, unless proper correction methods are used, horizontal distances between two locations determined by the GNSS method will differ from the measurements that are made by traditional survey methods. This difference between the two measurements is often referred to as the grid-to-ground problem. This article provides a process to address this problem.